Molecular characterization of rare G3P[9] rotavirus strains isolated from children hospitalized with acute gastroenteritis - Khamrin P. (2014)
In 2004, an epidemiological survey of human rotavirus infection in Chiang Mai, Thailand detected two uncommon human rotavirus strains (CMH120/04 and CMH134/04) bearing AU-1-like G3P[9] genotypes in 1 year old children hospitalized with acute gastroenteritis. The CMH120/04 and CMH134/04 rotavirus strains were characterized by molecular analyses of their VP6, VP7, VP8*, and NSP4 gene segments as well as the determination of RNA patterns by polyacrylamide gel electrophoresis (PAGE). Analysis of the VP8* gene revealed a high level of amino acid sequence identities with those of P[9] rotavirus reference strains, ranging from 94.9% to 98.3%. The highest identities were shared with the human rotavirus AU-1 strain at 97.8% and 98.3% for CMH120/04 and CMH134/04 strains, respectively. Analysis of the VP7 gene sequence revealed the highest identities with G3 human rotavirus strain KC814 at 96.6% and 96.2% for CMH120/04 and CMH134/ 04 strains, respectively. Based on the analyses of VP7 and VP8* genes, CMH120/04 and CMH134/04 belonged to G3P[9] genotypes. In addition, analyses of VP6 and NSP4 sequences revealed a VP6 subgroup (SG) I, with NSP4 genetic group C specificities. Moreover, both strains displayed a long RNA electrophoretic pattern. The finding of uncommon G3P[9] rotaviruses in pediatric patients provided additional evidence of the genetic/antigenic diversities of human group A rotaviruses in the Chiang Mai area of Thailand. © 2007 Wiley-Liss, Inc.